Analisis Putusan Nomor 25/G/2019/PTUN.Kdi Terkait Penerbitan SKKT oleh Kepala Desa Tapunggaya di wilayah Izin Usaha Pertambangan (IUP) PT. ANTAM Tbk - Yunita Nur Khasanah*; Rahmania Ramadhani; Sabiila Yassarhah; Yuli Febrianti (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This article analyzes the decision Number 25/G/2019/PTUN.Kdi regarding the Land Ownership Certificate issued by the Head of Tapunggaya Village over the Mining Business Permit area of PT. ANTAM Tbk. The analysis is done by reference to mining law and agrarian law. This research was organized with the aim of evaluating validity and strength of the Land Ownership Certificate and its implications for the rights of PT. ANTAM Tbk in execution mining activities in the area. This research methodology used is a normative approach with case analysis techniques. The results of the analysis in the study show that Certificate of Land Ownership issued by the Head of Tapunggaya Village does not have sufficient legal force because the area is under the Mining Business License of PT. ANTAM Tbk. The implication of this decision is that PT. ANTAM Tbk has the right to carry out mining activities in the area and this decision provides legal certainty for all related parties.